NEW METHOD OF PREVENTION OF IRONDEFENSE ANEMIA IN PREGNANT TEENS - E. S. Mikhaylin; L. A. Ivanova; A. G. Savitsky; M. M. Shilo; I. V. Berlev (Архивъ внутренней медицины, 2018)
The paper presents an assessment of the effectiveness of the method proposed by the authors for the prevention of iron deficiency anemia in minor pregnant women. In the first stage, 593 histories of childbirth were retrospectively analyzed (group 1 — minors 13-15 years (n = 49), 2 group — minors 16-17 (n = 434), 3rd group — middle reproductive age (n = 110) ). In the second stage, a prospective study of the frequency and structure of anemia of pregnant women was carried out (group 1 — minors aged 13-15 years (n = 17), group 2 — minors 16-17 (n = 127), 3rd group — women of middle reproductive age (n = 110)). At the III stage, minor pregnant women were divided into two groups: in 1 (main) group (n = 144), iron deficiency anemia was prevented according to the method we proposed; in the 2nd group (comparison group) traditional therapy with iron preparations was carried out at the appearance of signs of anemia. The essence of the proposed method is that an minor pregnant woman, without waiting for laboratory signs of anemia, is examined for ferritin in venous blood, and at a value below 35 ng/ml, oral iron preparations are prescribed in conventional preventive doses for a period of 3 months, and if through three months the content of ferritin in the venous blood is again below 35 ng/ml — the intake of iron-containing preparations continues for another 3 months. The use of the proposed method contributed to a significant decrease in the incidence of anemia in minor pregnant women. The proposed method of preventing iron deficiency anemia in minor pregnant women helps to reduce the frequency and severity of anemia in this complex category of patients.